Mosquitoes in an Urban Zoo: Identification of Blood Meals, Flight Distances of Engorged Females, and Avian Malaria Infections - Martínez-de la Puente, Josué; Soriguer, Ramón; Senar, Juan Carlos; Figuerola, Jordi; Bueno-Mari, Rubén; Montalvo, Tomás (Frontiers in Veterinary Science, 2020)
Zoological gardens are home to a large number of vertebrate species and as such are suitable sites for both mosquito breeding and maintenance. They are excellent places for entomological studies of mosquito phenology, diversity and blood-feeding patterns, as well as for xenomonitoring. During 2016, we sampled mosquitoes in Barcelona Zoo and used molecular methods to determine their blood-feeding patterns and the prevalence and diversity of avian malaria parasites. We also estimated the flight distance of engorged mosquitoes in the area. Overall, 1,384 adult Culex pipiens s.l., Culiseta longiareolata and Aedes albopictus were captured. Birds dominated the diet of Cx. pipiens s.l. (n=87) and Cs. longiareolata (n=6), while humans were the only bloodmeal source of Ae. albopictus (n=3). Mosquitoes had a mean flight distance of 95.67 m after feeding on blood (range 38.71–168.51 m). Blood parasites were detected in the abdomen of 13 engorged Cx. pipiens s.l., eight of which had fed on magpies. Four Plasmodium lineages and a single lineage of the malaria-like parasite Haemoproteus were identified. These results suggest that Cx. pipiens s.l. is involved in the local transmission of avian Plasmodium, which potentially affects the circulation of parasites between and within wildlife and enclosed animals. Vigilance regarding possible mosquito breeding sites in this zoo are thus recommended.